Voltage generation in piezoelectric energy harvesting with magnet: FEA simulation and experimental analysis - Jaafar, Muhammad Imran; Rabah, Hossameldin M.M.M.; Nordin, Nor Hidayati Diyana; Abdul Muthalif, Asan Gani; Wahid, Azni Nabela (UTHM Publisher, 2021)
Energy harvesting devices are needed as an alternative to batteries as it is costly to power up wireless sensor network. However, the power generated and operating bandwidth for the typical energy harvester are still compromised. Therefore, in this work, the use of permanent magnet in Piezoelectric Energy Harvester (PEH) is proposed to increase the operating bandwidth. A simulation study was conducted using COMSOL Multiphysics software to observe the effect of mechanical tuning using magnet on the voltage produced. It shows that PEH with oscillating magnetic field is capable of reaching generated peak power of 0.775 mW and increase the operating bandwidth by 10%. Experimental setup was also fabricated to further validate the observation at different polarities and varying distances with permanent magnets. It is observed that while the peak power achieved in the attractive mode is smaller as compared to its counterpart, however, its bandwidth is larger.